A review of L10 FePt films for high-density magnetic recording. (12th March 2008) - Chen, Jingsheng; Sun, Chengjun; Chow, Gan Moog
In this paper, we have reviewed the current status of the study of L10 FePt alloy films for the application for ultra-high-density magnetic recording. For practical realisation of L10 FePt as recording media, issues such as decreasing preparation temperature, easy axis control, and reduction in media noise must be solved. The Ag-doping and strain-inducing methods are the most promising to lower the ordering temperature. However, the films using Ag-doping and strain-inducing method usually showed lower coercivity due to significant amount of defects in the film. Two methods, epitaxial growth and non-epitaxial growth, were introduced to control the easy axis and each method had its advantages and disadvantages. Media noise was also reduced by pinning method.